Kowledge capital and total factor productivity - Welfe, Władysław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2007)
Development of “new economies” leading to economies mostly based on knowledge implies the construction of new long-term macroeconometric models. They should incorporate the impacts of new technologies being endogenized, as well as human capital. The paper discusses several issues related to the extension of the notion of production function. They cover first of all the measurement and explanation of knowledge capital and of total factor productivity (TFP), the role of domestic and foreign R&D expenditures, as well as educational expenditures. The discussion is extended to include the empirical results obtained in the world literature
Argumenta Oeconomica, 2007, No 1-2 (19), s. 211-236
Keywords: Knowledge economy; technical progress; production functions; total factor productivity; R&D expenditures; human capital